A Stimulus-Response Framework to Investigate the Influence of Continuous Versus Interval Walking Exercise on Select Serum Biomarkers in Knee Osteoarthritis. (April 2019) - Jayabalan, Prakash; Gustafson, Jonathan; Sowa, Gwendolyn A.; Piva, Sara R.; Farrokhi, Shawn
Abstract : Objective: The aim of the study was to compare changes in the concentration of serum biomarkers in response to continuous versus interval walking exercise in participants with knee osteoarthritis. Design: This study used a two-phase sequential design. Twenty-seven participants with unilateral knee osteoarthritis completed two separate treadmill walking sessions: (1) continuous 45-min walking exercise and (2) three 15-min bouts of walking exercise separated by 1-hr rest periods for a total of 45 mins in an interval format. Participants reported their knee pain using the numeric pain rating scale and serum levels of biomarkers associated with tissue turnover (cartilage oligomeric matrix protein), inflammation (tumor necrosis factor α), and pain (neuropeptide Y) were evaluated at baseline and every 15 mins for both conditions. Results: Continuous walking resulted in a cumulative increase in cartilage oligomeric matrix protein concentration up to 45 mins, whereas interval walking was associated with return of cartilage oligomeric matrix protein concentrations back to baseline at 45 mins. There were no significant changes in tumor necrosis factor α and neuropeptide Y concentration during walking. There was a significant increase in pain compared with baseline in the continuous walking regimen only. Conclusions: Incorporating rest breaks in walking regimens may affect the potential deleterious effects of longer continuous bouts on the knee joint as well as limit pain during exercise.